Gender Representation In The English Textbook: “My Next Words” For Fourth-Grade Students - Reviana Azzahra Karsena; Ellisa Indriyani Putri Handayani (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
This study was aimed to investigate gender representation in an English Textbook entitled Student’s Book My Next Words for Elementary School which published by The Republic of Indonesia’s Ministry of Education and Culture in 2021 and students opinion related gender equality. This study used a qualitative research with content analysis design. Porecca’ (1984) framework was adopted for analyzing the female and male representation in the English textbook: omission (the ratio of females to males) in texts and illustrations, firstness, occupational visibility, noun, masculine generic construction, and adjective. The result of gender omission is not too high with the average ratio of females to male 1:1.03. For social dominance was not found in the textbook. The result of this study from the variants of firstness, occupation, noun, and masculine generic for males are varier than for females. Some stereotypes were found such as cooking for females’ activity and the breadwinner role for males. A limitation of the study is this research focuses on one textbook only. Thus, this study can’t be generalized. For this purpose, another study with a larger sample would be required a deeper analysis of the picture of the EFL textbook.